QUEM TEM MEDO DOS ESTUDOS CULTURAIS? - de Medeiros, Rosângela Fachel (Organon, 2004)
The main objective of this article is to discuss the viewpoints of some of the most known Braziliancomparative theorists regarding the difficult relation between Cultural Studies and Comparative Literature inBrazil, in an attempt to develop a brief review of the different ways of considering Cultural Studies and theirpresence in the comparative action.